An Update on Florida’s Artificial Reefs: Recent Research and What It Means for Florida - Edward V. Camp; Lisa Chong; Angela B. Collins; Holly Abeels; Keith Mille; Brittany Hall-Scharf; Ana Zangroniz; Scott Jackson; Shelly Krueger; Victor Blanco (EDIS, 2022)
As coastal managers and practitioners continue placing artificial reefs in marine waters, the scientific understanding of the effects and implications of artificial reefs is changing. It is especially important for resource managers and Extension and outreach personnel, as well as the interested public, to keep aware of these changes as they occur, but usually scientific studies are first published in peer-reviewed journals that may be inaccessible. This publication describes some of the most recent artificial reef studies that are likely to be especially relevant to Florida. Each is summarized and its potential relevance to Florida described. This is not a complete record of recent research, but it should help the interested public, managers, educators, and outreach personnel stay informed of recent developments in artificial reef science that should be considered when making decisions about artificial reefs.